2002
DOI: 10.1055/s-2002-26755
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of N(G)-Nitro-L-arginine Methyl Ester on the Anti-Adrenergic Response Elicited by Ayanin in the Pithed Rat

Abstract: In this study we evaluated the anti-adrenergic response elicited by ayanin, a flavonoid compound isolated from Croton schiedeanus Schlecht, in the pithed rat, and the inhibitory effect of NO synthase inhibitor N(G)-nitro-L-arginine methyl ester (L-NAME), and its acute toxicity profile in mice. In pithed rats ayanin (5 - 50 mg/kg i. v.) caused a dose-dependent decrease in the pressor and chronotropic responses induced by intravenous noradrenaline administration (0.25 microg/kg). This anti-adrenergic response wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
(14 reference statements)
0
7
0
1
Order By: Relevance
“…In previous work we reported the hypotensive and vasorelaxant eOE ects in rats of Croton schiedeanus Schlecht (Guerrero et al 2001), a medicinal plant used in Colombian folk medicine for hypertension. From this plant, we isolated ayanin, a bio¯avonoid that, in-vitro, induces relaxation in Wistar rat aorta mediated by endotheliumdependent NO production and subsequent activation of guanylate cyclase (unpublished data) and that, in-vivo, exerts protective cardiovascular eOE ects against the increase in blood pressure and heart rate also through a mechanism that depends on the NO}cyclic guanosine monophosphate (cGMP) pathway (Guerrero et al 2002). Further phytochemical fractionating of this plant led us to the identi® cation of quercetin 3,7-dimethyl ether (QDME).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we reported the hypotensive and vasorelaxant eOE ects in rats of Croton schiedeanus Schlecht (Guerrero et al 2001), a medicinal plant used in Colombian folk medicine for hypertension. From this plant, we isolated ayanin, a bio¯avonoid that, in-vitro, induces relaxation in Wistar rat aorta mediated by endotheliumdependent NO production and subsequent activation of guanylate cyclase (unpublished data) and that, in-vivo, exerts protective cardiovascular eOE ects against the increase in blood pressure and heart rate also through a mechanism that depends on the NO}cyclic guanosine monophosphate (cGMP) pathway (Guerrero et al 2002). Further phytochemical fractionating of this plant led us to the identi® cation of quercetin 3,7-dimethyl ether (QDME).…”
Section: Introductionmentioning
confidence: 99%
“…Although in previous studies we have reported the antihypertensive and vaxorelaxant activities of the ethanolic extract from Croton schiedeanus, 15) the diterpenoids 1-6 did not show any significant vasodilator effect in an in vitro screening in rat aortic ring. Extraction and Isolation The dried and triturated aerial part of C. schiedeanus (8 kg) was soaked in 96% EtOH (35 l) at room temperature for three days.…”
mentioning
confidence: 59%
“…subpubescens [ 28 ]. This compound has been reported to have antiasthmatic activity [ 257 ], protective cardiovascular effects [ 258 ], vasorelaxant activity [ 259 ], anti-inflammatory activity [ 260 ], and anticancer properties [ 261 ]. In order to evaluate the use of different natural compounds on the treatment of NTDs, Mahmoud et al [ 262 ] tested ayanin for antiprotozoal activity.…”
Section: Biological Activitymentioning
confidence: 99%